Cellular responses of Bacillus subtilis and Escherichia coli to the Gram stain. - Beveridge, T J (1983)
Exponentially growing cells of Bacillus subtilis and Escherichia coli were Gram stained with potassium trichloro(eta 2-ethylene)platinum(II) (TPt) in place of the usual KI-I2 mordant. This electron-dense probe allowed the staining mechanism to be followed and compared with cellular perturbations throughout the staining process. A crystal violet (CV)-TPt chemical complex was formed within the cell substance and at the cell surface of B. subtilis when the dye and Pt mordant were added. The ethanol decolorization step dissolved the precipitate from the cell surface, but the internal complex was retained by the cell wall and remained within the cell. This was not the case for E. coli; the ethanol decolorization step removed both surface-bound and cellular CV-TPt. During its removal, the outer membrane was sloughed off the cells until only the murein sacculus and plasma membrane remained. We suspect that the plasma membrane was also perturbed, but that it was retained within the cell by the murein sacculus. Occasionally, small holes within the murein and plasma membrane could be distinguished through which leaked CV-TPt and some cellular debris. Biochemical identification of distinct envelope markers confirmed the accuracy of these images.